Envoltória de resistência do Concreto Compactado com Rolo (CCR), incluindo o efeito escala - Junqueira, Pedro João Barbosa (2010)
The dam construction tecnology with roller compacted concrete has undergone noticeable improvements in the areas of concrete technology and enforcement procedure. One can cite the enrichment of roller compacted concrete dam face and the whole sequence leading to obtaining such enrichment, in a short-term enforcement, by the least cost and with the guarantee of the security needed, as one of those remarkable improvements. This work, however, tries to contribute with the theme of the properties of concrete and incorporates basic issues of materials science to set a failure criterion to the results of combined loadings tests performed in RCC specimens of varied sizes, made with the same dosage of Junqueira et al. (2008). The goal is to predict the real strength of the roller compacted concrete dam. Therefore, tests of diametral compression, uniaxial compression, triaxial compression and direct shear tests were performed in RCC specimens of different sizes. The results of such tests were presented using tables and graphs which showed a fall of resistance with increasing the size of the specimen tested face of such loadings. Finally, the data from all trials of this work and of Junqueira et al. (2008) were gathered and studied, so as to increase the precision of the strength envelope of Hoek and Brown set.